The Politics of Parent Choice in Public Education The Choice Movement in North Carolina and the United States - Lewis, Wayne D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This is the story of North Carolina parent choice advocates' push for the creation and expansion of choice policies. The exploration of the politics, ideology, and interests surrounding parent choice includes but also stretches beyond the most frequently discussed choice policies of charter schools, school vouchers, and tuition tax credits.
Keywords: Science; Science; Science, general